Discrete Modelling of Wave Propagation in Bars with Piecewise-Linear Characteristics - Szcześniak, Z. (Engineering Transactions, 1992)
A method is proposed to model one-dimensional wave propagation problems in a discrete manner as applied to the material with piecewise-linear stress-strain relationship in loading and rigid-elastic behaviour in unloading. The method consists in a simple combination of basic models, i.e. an elastic model and a plastic model with rigid unloading to obtain a combined model. It turns out to be accurate and effective. Numerical algorithm is described. Errors are discussed and an example of unloading stress wave is given.